Driving the future of value-based healthcare in the Gulf Cooperation Council: a roadmap for achieving sustainable access to specialty pharmaceuticals - Hamad, Anas; Al-Jedai, Ahmed; Ojeil, Rita; Al-Jazairi, Abdulrazaq Sheikh; AlAssy, Adel; AlRuthia, Yazed S.; Al Naeem, Waiel; Almudaiheem, Hajer; Alsaadi, Mouza; Alagil, Nada; Wahba, Lina; Marghalani, Abdulmohsin; et al. (Frontiers in Public Health, 2025)
Gulf Cooperation Council (GCC) countries are undergoing a critical transformation in their healthcare systems. This empowers them to address the rising burden of complex diseases, including rare diseases, cancer, neurological disorders, and immunological illnesses, which involve a high cost of therapy. A strategic shift from volume- to value-based healthcare (VBH) emphasizes sustainability, enhanced accessibility, and improved health outcomes through innovation. GCC’s healthcare is marked by universal coverage and a shifting landscape of public-private partnerships. Rising pharmaceutical costs, especially for specialty drugs, continue to challenge budget sustainability. VBH offers a strategy to align healthcare expenditure with patient outcomes. This framework is supported by global and regional models such as managed entry agreements (MEAs), multi-criteria decision analysis, and real-world evidence (RWE). These models provide guidance for reimbursement strategies and support decision-making regarding high-value treatments. The GCC nations are also progressing towards policy discussion, but face challenges related to infrastructure, regulation, and workforce capacity. The Department of Health (DOH) in Abu Dhabi, which is a governmental health authority in the United Arab Emirates, has officially established a dedicated HTA unit to evaluate and assess new health technologies for evidence-informed decision making. This review highlights specialty care priorities and proposes target strategies such as expanding genetic databases, implementing screening programs, and establishing risk-sharing agreements to improve affordability, particularly for rare diseases. A consensus-driven phased roadmap for GCC-wide VBH adoption is recommended. This includes a focus on MEAs and patient-reported outcome measures, mid-term harmonization of health technology assessments (HTA) and RWE development as well as long-term establishment of digital ecosystems and value-based pricing platforms. Equitable and collaborative policies will be essential to achieving sustainable and inclusive healthcare systems across the GCC.